Ion Composition Measurement with a Rocket-Borne Mass Spectrometer at Syowa Station - Nobuyoshi FUGONO; Takeshi SUITSU; Nobuyoshi FUGONO Takeshi SUITSU Iwao IWAMOTO (National Institute of Polar Research, 1975)
A positive ion mass spectrometer was flown on the S-210JA-12 rocket at Syowa Station in the Antarctic Region (69°00'S, 39°35'E), at 13:00 LT, on Feb. 11, 1972. Measurements were obtained from about 108 km, its apogee, to about 80km on descent. A few metal ions in E-region and hydracted ions in D-region of the ionosphere were observed in addition to the main NO^+ and O^+_2 profiles.